Sörmländska låtar av högsta klass: Värdetillskrivning, kvalitativa källkedjor och låthäftet 56 sörmländska låtar - Eriksson, Karin L. (Puls – musik- och dansetnologisk tidskrift, 2025)
When the Södermanland Fiddlers’ Association published the book 56 sörmländska låtar (56 tunes from Södermanland) folk tunes arranged for violin and viola in 1956 by the music publisher AB Nordisk Folkmusik (Nordic folk music Ltd.), it was part of a larger aim to promote the survival of Sörmland folk music tradition. The booklet contains tunes arranged for fiddle and in some cases viola, but also prefaces and concluding comments. The purpose of the study is to use these comments to illustrate how a folk music repertoire is charged with values and how this attribution of values can be expressed. This is done through a close reading of the commentaries, with a particular focus on the provenance markings in them. But also on how the representativeness of the songs is written, references to expert authorities, and the importance of securing the qualitative source chains of the tunes. The study shows the importance of both placing the tunes in a Sörmland context and, when this is done, of securing the quality of the tunes’ transmission history in various ways. The article concludes with a brief discussion of how the values of use and representation are expressed both in the booklet as such and in the preceding correspondence and other related material. Finally, it is noted that the booklet should be seen as a commercial product and that it was important for the publisher to be able to finance its activities in order to continue to promote Swedish folk music through the publication of sheet music.